Lost in time : a Blue Bloods novel / Melissa de la Cruz. - De la Cruz, Melissa, 1971- (New York : Hyperion, 2011)
Schuyler Van Alen and her love Jack Force go their separate ways after their trip to Florence, Italy, with Schuyler going to Egypt to fulfill the Van Alen legacy, while Jack returns to Manhattan to face his twin sister, Mimi, but things get even more complicated when Mimi jets off to Egypt while the Coven threatens to fall apart around her.
Keywords: Vampires -- Fiction; Wealth -- Fiction; Egypt -- Fiction; New York (N.Y.) -- Fiction